Dictionary of archaeological terms : English-Greek/Greek-English - Koutsoumpos, Nikos (Archaeopress, 2012)
Continuing the Archaeopress series of pocket-sized Dictionaries of Archaeological Terms, here is a dictionary of useful terms compiled to assist in the reading of archaeological books and publications, and in the writing of papers and articles, in both English and Greek. It covers Aegean prehistory through to Hellenistic and Roman times.